Quality and Organizational Innovation: Competitiveness Tools in the Table Grape System - Maycotte de la Peña, Mayra Lucía; Montaño Silva, Karen; Robles Parra, Jesús Martín; Paz-Luna, Jesús Lauro (Mercados y Negocios, 2023)
The research seeks to analyze quality management strategies as organizational innovation practices incorporated by table grape-producing organizations and their relationship with competitiveness. The data was obtained by elaborating a semi-structured interview script, which was applied to the managers or responsible people of the Sonoran table grape-producing organizations. The results allow us to recognize the main innovations organizations incorporate, specifically those related to organizational innovation. It was concluded that quality and organizational innovation are considered essential practices to generate competitive advantages in organizations since they generate knowledge, learning, and skills that drive decision-making aimed at business success.